If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5*(9-2)+(7*5+7)/6=0
We simplify the equation to the form, which is simple to understand
-5*(9-2)+(7*5+7)/6=0
Simplifying:
-5*(9-2)+(+35+7)/6=0
Simplifying terms in parentheses
-5*(+7)+(+35+7)/6=0
Simplifying terms in parentheses
-5*(+7)+(+42)/6=0
Reorder the terms in parentheses
+(-35)+(+42)/6=0
Remove unnecessary parentheses
-35+(+42+)+/6=0
Reorder the terms in parentheses
-35+(+7)=0
Remove unnecessary parentheses
-35+7=0
We move all terms containing to the left and all other terms to the right.
0=0+35-7
We simplify left and right side of the equation.
0=+28
0=28
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 5+6x=4x+15 | | 3x+(-11y)+(-12x)+7y= | | 18y-21y= | | 6n+7=14 | | x+3x(9)=40 | | 18a=4a-4(a+3) | | 5-7x+6+5x+3x-3=5+2*5 | | 5(3a-1)=-95 | | 2.6x+18=24+22 | | 2.6x+18=24 | | -2m+13=-3 | | 7-9(5x)=20 | | -3(-5k-6)=108 | | 4x*7=49 | | h(t)=1.86t^2+4t-1.86 | | 6+2x=20x | | 6+2x=18x | | -104=4(5p-6) | | 4(x-2)-(2x-5)= | | 4-v+2v=8 | | 3(5+2x)=2x | | 2x=3(5+6x) | | 2b-b+5b=4a | | (-4+xyz)-(5+xyz)= | | 8x=4x-24 | | (7x+2y)+(-3y+x)= | | 4.9*x^2-13*x-23=0 | | 7y=6y-8 | | 3.01i-1.52i= | | p-30=6(h-6) | | -79h-(-9h)= | | -79h-(-9)= |